DEVELOPMENT OF SOCIAL STUDIES TEACHING MATERIALS BASED ON ETHNOPEDAGOGY FOCUSING ON FAMILY AND SOCIETY TRADITIONS OF MADURA TO ENHANCE COMMUNICATION SKILLS OF 3RD GRADE ELEMENTARY SCHOOL STUDENT - Oktaviani Adhi Suciptaningsih; Amina Divina P; Ari Sapto (Jurnal PIPSI (Jurnal Pendidikan IPS Indonesia), 2024)
Developing communication skills in elementary school students is a very important need. The level of mastery of children's communication skills not only affects intellectual development through learning effectiveness, but also affects the social process and overall personal development of students. Initial studies show that 77% of students have not shown communication skills, while 23% of students show quite good progress with teacher direction and guidance. In addition, the teaching materials used, namely the science textbook, have not been effective in developing students' communication skills. So that the communication skills of 3rd grade students have not been formed completely. One of the school's efforts to improve communication skills is the use of models, methods, and media according to student needs and meet the demands of learning in the society 5.0 era in elementary schools. The development of ethnopedagogy-based social studies teaching materials on Madurese family and community traditions to train the communication skills of 3rd grade elementary school students can be an alternative solution to the problem. By using the research and development method of analysis, design, development, implementation, and evaluation (ADDIE), the results of improving communication skills were quite satisfactory. The results of the validation of language experts obtained a percentage of 80% and validation of teaching material experts by 76%, so it can be concluded that the teaching materials that have been developed are quite valid and can be used but with improvements. Meanwhile, the results of the trial obtained an assessment percentage of 84% or valid for use according to expert practitioners, while the percentage of student assessments was 87.4% or can be said to be very interesting. Based on the results of observations of learning with ethnopedagogy-based social studies teaching materials that have been developed, there is an increase in students' communication skills, especially oral communication, through various activities and works produced such as mini podcasts and mini vlogs.